Normas de gênero e heteronormatividade em uma escola de educação básica em Aracaju (SE) - Oliveira, Danilo Araujo de (2017)
This dissertation analyzed the functioning and performance of the norms of gender and heteronormativity in a school of basic education. A post-critical position was adopted, considering the contributions of this type of approach to question the school practices, problematizing and stimulating new ways of thinking the formal pedagogical spaces. The methodological approach was qualitative, based on the conducting of open interviews with 16 teachers (12 women and four men) and the data analysis inspired by Discourse Analysis. The results of the research inform us that normalizing discourses function as educational demands, conferring gender intelligibility to the bodies, marking and also regulating, those who present performance that distance from and break the norms of gender, based on heteronormative discourse. It was also observed that, essentialist notions of gender and sexuality are triggered, learned and taught, through the crossing of biological and religious discourses in the narratives defining and attaching two possible and opposing gender identities: male-man / female-woman. The discourses that cross the teachers' narratives update a hegemonic masculinity and femininity norm, reinforcing the (re) production of compulsory heterosexualization in the researched curriculum, with few experiences of subversions.